Case report: rupture of popliteal artery aneurysm - Altino Ono Moraes; Rogério Yoshikazu Nabeshima; Felipe Franchini Rezende; Ericsson Fernando Viotto; Claudio Ricardo Bogdan (Jornal Vascular Brasileiro, 2015)
An 83-year-old female patient with a history of prior endovascular treatment to repair an abdominal aortic aneurysm presented with intense pain and edema in the left leg, with hyperemia and localized temperature increase. Doppler ultrasonography revealed a voluminous aneurysm of the popliteal artery with a contained rupture, and hematoma involving the popliteal fossa and the medial and anterior surfaces of the knee causing compression of the popliteal vein. Endovascular repair was accomplished with covered stents and the rupture was confirmed. during the procedure The aneurysm was excluded and the signs and symptoms it had caused resolved completely, but during the postoperative period the patient developed sepsis of pulmonary origin and died.